Pathology of Bovine Tuberculosis in Three Breeds of Dairy Cattle and Spoligotyping of the Causative Mycobacteria in Ethiopia - Ambaw, Mulualem; Gelalcha, Benti Deresa; Bayissa, Berecha; Worku, Adane; Yohannis, Aster; Zewude, Aboma; Ameni, Gobena (Frontiers in Veterinary Science, 2021)
BThe different breeds of cattle were observed to have variable degree of susceptibility to bovine tuberculosis (bTB). The screening of bTB was conducted on 720 dairy cattle consisting of three breeds using the single intradermal cervical comparative tuberculin test (SICCT) test. Besides, 43 SICCT test positive cattle were used to compare the severity of pathology of bTB was among the three breeds and to identify the causative mycobacteria using spoligotyping. The overall SICCT test positivity was 17.92% (129/720) by pooling all animals in the three farms. There was a significant difference in SICCT test positivity among the three breeds (2 =71.06; p<0.001); the highest (25.34%) was recorded in the cross breed followed by the Boran breed (10.08%) while the least (3.14%) was recorded in the Jersey breed. On other hand, the highest median pathology score (10.0, interquartile range, IQR = 6.0 – 17.0) was recorded in Boran followed by cross (5.0, IQR = 3.5 – 7.5) while the least (3.0, IQR = 2.25 – 3.0) was recorded in Jersey. Thus, the difference in the median pathology scores was significant (Kruskal Wallis 2(2) = 18.78, p < 0.001) among the three breeds. Furthermore, multivariate analysis using ordinal logistic regression by considering age, sex, breed, reproductive status, and location of the farms also showed significant (2(2) = 11.97, p < 0.01) difference in pathology scores among the three breeds of cattle. Even at a single herd level at Holeta, the difference in severity of pathology between the Boran and cross breeds was significant (U = 33.5; p < 0.01). Culture positivity was 39% in 108 suspicious tissues. Fourteen Mycobacterium bovis (M. bovis) and two Mycobacterium tuberculosis (M. tuberculosis) were isolated from the lesions. All the 14 M. bovis isolates belonged to SB0912 while the two M. tuberculosis belonged to SIT54. In conclusion, although the frequency of SICCT test positivity was high in the crossbreed, more severe pathology was observed on the Boran (zebu) breed. In addition, M. tuberculosis was isolated from TB lesions of dairy cattle demonstrating the role of M. tuberculosis in causing TB in cattle.